The effect of reducing work rate on total work done, and exercise tolerance, during severe intensity exercise - Welburn, A.; Bailey, S.; Ferguson, R. (Journal of Science and Cycling, 2024)
Introduction The hyperbolic relationship between power output and time to exhaustion during high-intensity exercise can be described by a power asymptote, critical power (CP), and curvature constant, W'. CP demarcates the heavy and severe intensity domains. W' it is considered a fixed and finite amount of work that can be completed above CP which when depleted exhaustion will occur, or work rate has to be reduced below CP (Fukuba et al. 2003; Morton 2006; Poole et al. 1988) The assumption that W` is a fixed parameter has been challenged. Although Fukuba et al. (2003) originally demonstrated that after initially depleting 50% of W` during severe intensity exercise, subsequently increasing or decreasing the work rate, did not result in any changes to the total work done. In contrast, Dekerle et al. (2015) showed that when work rate was reduced (from 140% to 105% of CP), 20% more work above CP was done than precited. This observation leads to the possibility that W' may not be fixed which will have implications for predicting exercise tolerance during variable efforts (i.e., pacing), as well as the modelling of W` depletion/reconstruction. Therefore, the aim of this study is to (i) assess changes in total work done above CP when the work rate is reduced during severe intensity exercise (ii) assess if reducing the work rate just prior to exhaustion allows work to continue above CP.